MECHANISM CREATING CONDITIONS FOR PERSONAL PROFESSIONAL AND PSYCHO-PHYSICAL DEVELOPMENT AND SELF-REALIZATION, SOCIAL ACTIVITY AND EMPLOYMENT YOUNG PEOPLE - Goncharenko, Iryna M.; Krakhmalova, Nina A. (Journal of Strategic Economic Research, 2023)
Based on previous studies of the main components of the Hackathon-ecosystem of social integration, taking into account the conditions of the new outbreak of the Covid-19 pandemic; the authors of the article proposed a general mechanism for the integration of the Hackathon ecosystem into the ecosystem of a higher education institution, which will allow organizing a complex interaction of interactive tools of the innovative chain of developing the human potential of youth, improving national security in the context of preventing a new outbreak of the Covid-19 pandemic. In particular, the article proposes an organizational and management complex that ensures the creation and functioning of Hackathon-ecosystems of the university. It was determined that this complex is a system that can be formed by full-time units of the university and provides legal, organizational, managerial, financial, technical and other support to the Hackathon-ecosystem of the university, manifested in the form of the transfer of resources and information. The most significant elements of this complex are considered – the mechanism for creating the Hackathon-ecosystem of the university, the mechanism for supporting its activities, and the mechanism for administrative and managerial control. The study of the mechanism made it possible to identify a set of problems of organizational and managerial support, which may have a negative impact on the activities of the Hackathon-ecosystem of the university. It is suggested that the effectiveness of the University Hackathon-ecosystem functioning should be determined by the scientific, managerial, and material-technical task formed on the basis of the university, which forms and determines the features of the construction of its innovative ecosystem.